Rancangan Saluran Tebuka pada Sistem Penyaliran Tambang di PT Hasnur Riung Sinergi Jobsite PT Bhumi Rantau Energi, Kabupaten Tapin, Provinsi Kalimantan Selatan - Atok, Roy Andrew Ericson; Adnyano, A. A. Inung Arie (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2020)
PT Hasnur Riung Sinergi conducts coal mining using the open pit method, so that mining activities are directly related to outside. The problem is condition of the trench that unable to drain run off, so that makes overflows and inundates the roads and other mining areas. The research aims to design a trench that able to drain the planned run off and calculate the cost of making a trench. The method used is to calculate run off flow to determine the dimensions of the trench, then calculate the productivity of the machine to determine the cost of fuel requirements and the wages of the heavy equipment operator in making the trench. Based on the analysis of rainfall data obtained rainfall intensity of 53.58 mm/hour. There are 7 catchment areas that produce different amounts of run off. Design of a trapezoidal trench for each DTH, the trench on DTH 1, DTH 2, DTH 3, DTH 4 will be made in the pit and useful for flowing run off into the pit leading to the sump, while the trench on DTH 5, DTH 6, DTH 7 will be made outside the pit and useful for flowing run off that is outside the pit to the settling pond. The trench manufacturing work requires 2 PC200 komatsu backhoe machines with excavation time of 11 days. The cost to purchase fuel is Rp.27.846.000 and the cost to pay the operator is Rp.2.970.000. The total cost required for the work of making trenches is Rp.30.456.000. The design was made as a reference for companies in making trenches in the mining area to control run off so as not to interfere with mining activities.